Economic Crisis and the End of Democracy: Politics in Newfoundland During the Great Depression - Overton, James (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1990)
Abstract The dominion of Newfoundland gave up responsible government in 1934. From then until 1949, when it joined Canada, Newfoundland was governed by a Commission responsible to the British government in Westminster. The ostensible cause of the collapse of democratic government in Newfoundland was a financial crisis and the country's impending bankruptcy triggered by a drastic fall in state revenue during the depression of the early 1930s. The financial side of the crisis, Newfoundland's economic weakness, and the broad politicalevents of the period have received considerable attention. But aspects of Newfoundland's internal politics have not received the attention they deserve. It has been noted that there was little opposition to the movement in favour of an end to democratic government developed in Newfoundland in the early 1930s. It is aspects of this movement that are examined in this paper. Why did people in Newfoundland not only accept, but in many cases openly work for, and end to responsible government? In trying to answer this question attention is focused on the actions of labour leaders and the political representatives of the working classes. In particular, the disillusion with democracy of two key reformers, JR. Smallwood, the founder of the first Newfoundland Federation of Labour, and William Coaker, the founder of the Fishermen's Protective Union, is explored.